2000
DOI: 10.1071/ea99011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molasses on the fermentation quality of wheat straw and poultry litter ensiled with citrus pulp

Abstract: In a 4 2 factorial design, mixtures of wheat straw, poultry litter and citrus pulp with 0 and 5% molasses [T1 (75:25:0), T2 (60:25:15), T3 (45:25:30), and T4 (30:25:45)] were ensiled for a period of 60 days in 20 L laboratory silos. Inclusion of 5% molasses had no significant (P>0.05) effect on pH, neutral detergent fibre, acid detergent fibre, acid detergent lignin contents and in vitro organic matter (OM) degradability. However, molasses decreased (P<0.05) the concentration of volatile fatty acids incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Consistent with our findings, Migwi et al [23] reported that when 5% molasses was added to the mixture of wheat straw+ broiler litter, no effect on silage pH was detected. However, when the proportion of CP increased from 0 to 30% in the silage, the pH declined markedly [23]. Similarly, when CP was ensiled alone, lactic acid concentration was negligible (1.02% of DM, after 14 d of ensiling; Figure 2).…”
Section: Co-ensiling Of Garlic Stalk With Citrus Pulpsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our findings, Migwi et al [23] reported that when 5% molasses was added to the mixture of wheat straw+ broiler litter, no effect on silage pH was detected. However, when the proportion of CP increased from 0 to 30% in the silage, the pH declined markedly [23]. Similarly, when CP was ensiled alone, lactic acid concentration was negligible (1.02% of DM, after 14 d of ensiling; Figure 2).…”
Section: Co-ensiling Of Garlic Stalk With Citrus Pulpsupporting
confidence: 93%
“…After 14 d of ensiling, the pH of GS 50%+CP 50% silage declined markedly, which is suggestive of successful silage fermentation that is known to slow down or inhibit the growth of fungi, molds, and yeasts [25]. Consistent with our findings, Migwi et al [23] reported that when 5% molasses was added to the mixture of wheat straw+ broiler litter, no effect on silage pH was detected. However, when the proportion of CP increased from 0 to 30% in the silage, the pH declined markedly [23].…”
Section: Co-ensiling Of Garlic Stalk With Citrus Pulpsupporting
confidence: 90%
See 1 more Smart Citation
“…Anastácio and Carvalho (2013) reported that SPP possessed more than threefold phenolic contents than the other plant tissues. Citrus pulp (CRP) is the by-product after juice extraction, containing high contents of fermentable substrates such as monosaccharides and non-starch polysaccharides (Migwi et al ., 2000). Deterioration of silage occurs during transferring and feed-out period in tropics and subtropics.…”
Section: Introductionmentioning
confidence: 99%